2023
DOI: 10.3389/fgene.2023.1270085
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress related genome-wide Mendelian randomization identifies therapeutic genes for ulcerative colitis and Crohn’s disease

Menglong Zou,
Qiaoli Liang,
Wei Zhang
et al.

Abstract: Background: Endoplasmic reticulum stress (ERS) is an important pathophysiological mechanism in ulcerative colitis (UC) and Crohn’s disease (CD). ERS-related genes may be influenced by genetic factors and intestinal inflammation. However, the role of ERS as a trigger or potential etiological factor for UC and CD is unclear, as the expression of ERS-related genes in UC and CD may be the cause or subsequent changes in intestinal inflammation. Here, we used a three-step summary data-based Mendelian randomization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Specifically, uses reduced glutathione (GSH) to convert hydrogen peroxide to water and oxidizes GSH to oxidized glutathione (GSSG), which in turn generates GSH again via other reducing enzymes, maintaining the relative balance of GSSH and GSSG (33). Zhou et al demonstrated the connection between endoplasmic reticulum stress-related genes and UC, and CD through a multi-omics approach and discovered that GPX1 expression lowered the risk of UC and CD (34). Oxidative stress leads to the inflammatory response exacerbated by oxidative damage to intracellular DNA, lipids, and proteins, which then triggers an inflammatory response in UC.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, uses reduced glutathione (GSH) to convert hydrogen peroxide to water and oxidizes GSH to oxidized glutathione (GSSG), which in turn generates GSH again via other reducing enzymes, maintaining the relative balance of GSSH and GSSG (33). Zhou et al demonstrated the connection between endoplasmic reticulum stress-related genes and UC, and CD through a multi-omics approach and discovered that GPX1 expression lowered the risk of UC and CD (34). Oxidative stress leads to the inflammatory response exacerbated by oxidative damage to intracellular DNA, lipids, and proteins, which then triggers an inflammatory response in UC.…”
Section: Discussionmentioning
confidence: 99%
“…SMR integrates and analyzes GWAS summary data with expression quantitative trait loci (eQTL) or DNA methylation quantitative trait loci (mQTL), developed to prioritize causal variation mediated by gene expression or DNA methylation [ 15 ]. Through the application of SMR, a study identified GPX1 as exhibiting a protective effect against UC, indicating its potential as a pharmacological target for these conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex role of ER in the normal physiological functions of the cell, dysfunctional behaviour of ER might have serious consequences [2,3,10,20]. ER stress is implicated in a wide range of human diseases [21,22], such as diabetes [23], non-alcoholic fatty acid disease [24], inflammations (including heart diseases [25] and inflammatory bowel disease [26,27]), neurodegeneration (Parkinson's disease [28], Alzheimer's disease [29] and Huntington's disease [30,31]) and also psychiatric diseases [32,33]. Since defects in the proper functioning of the ER are observed in most human diseases and the frequency of ER stress is also increased during aging [34][35][36], it is crucial to study and understand the dynamic behaviour of the regulatory system as comprehensively as possible.…”
Section: Introductionmentioning
confidence: 99%